A history of the world's religions - Noss, David S.; Noss, John Boyer (New York Macmillan College Pub., 1990)
A textbook for introductory college courses in the history of religions, published since 1949 as Man's religions. Surveys the origins, development, and divisions of the major religions of India, the Orient, and the Middle East. Each chapter includes a glossary, most with pronunciation indicated.
Religions of South Asia -- Early Hinduism : passage from ritual sacrifice to mystical union: Religion of the Vedic Age -- Brahmanism -- Caste -- Cermonila life -- Glossary -- Later Hinduism -- Religion as the determinant of social behavior -- Changes in Brahmanism -- Four goals -- Three ways -- Ordered society -- Ways of work -- Reflective mode -- Way of knowledge -- Upanishads -- Reflective models -- Six acceptable systems -- Devotional mode -- Way of devotion -- Bhagavad Gita -- devotional models -- Epics -- Puranas -- Deities -- Devotional life -- Issues -- Problems of the present -- Glossary -- Jainism -- Study in Asceticism -- Mahavira's manner of life -- Philosophy -- Ethics of Jainism -- Mahavira's followers -- Glossary -- Buddhism in its first phase -- Moderation in world renunciation -- Life of the founder -- Teachings of the Buddha -- Glossary -- Religious development of Buddhism -- Diversity in redemptive means -- Spread of Buddhism in India -- Southeast Asia -- Message of the Mahayana -- Mahayana philosophies of religion -- Mahayana schools of thought in China and Japan -- Buddhism today -- Glossary -- Sikhism : study in Syncretism -- Life and work of Nanak -- Nanak's teachings -- Political history of Sikhism -- Glossary -- Religions of east Asia -- Native Chinese religion and Daoism -- Basic elements of Chinese religion -- Daoism as a philosophy -- Daoism as magic and religion -- Glossary -- Confucius and Confucianism -- Study in optimistic humanism -- Man Confucius -- Teachings of Confucius -- Confucian school -- Rivals -- Champions -- New-Confucianism -- State cult of Confucius -- Religion in China in the modern period -- Glossary -- Great dispersion -- Making of the talmud -- Jews in the Middle East -- Judaism in the modern world -- Christianity in its opening phase -- Words and work of Jesus in Apostolic perspective -- World into which Jesus came -- Life of Jesus -- First phase -- Themes of Jesus' teaching -- Climactic events -- Apostolic age -- Early church -- Religious development of Christianity -- Ancient Catholic Church -- Eastern Orthodox churches -- Roman Catholic Church in the Middle Ages -- Protestant reformation -- Crosscurrents in the seventeenth and eighteenth centuries -- Catholicism in the modern world -- Recent theological trends -- Glossary -- Islam -- Religion of submission to God -- Beginnings -- Arabian beliefs and practices before Muhammad -- Prophet Muhammad -- Faith and practice of Islam -- Spread of Islam -- First five centuries of Muslim though --Shinto -- Native contribution to Japanese religion -- Background of Shinto -- Shinto myth -- Shinto in medieval and more recent times -- State of shinto -- Shinto and the warrior -- Shrine shinto today -- Domestic and sectarian shinto -- Glossary -- Religions of the Middle East -- Zoroastrianism -- Religion based on ethical dualism -- Iranian religion before Zoroaster -- Religion of the later avesta -- Zoroastrians of the present day -- Judaism in the early phases -- Hebrew origins to exile -- Religion of the pre-mosaic Hebrews -- Moses and the covenant with Yahweh (about 1250 B.C.E.) -- Yahweh and the Baals -- Prophetic protest and reform -- Babylonian exile -- Glossary -- Religious development of Judaism -- Rise of Judaism in the restoration period -- New trends of thought in the Greek and Maccabean periods -- Roman period to 70 C.E. -- Shi'ah alternative and regional developments -- Party (Shia) of 'Ali -- Further developments -- Islam and culture -- Issues in modern period -- Regional developments -- Movements toward innovation and syncretism -- Glossary -- References for quotations -- Suggestions for further reading -- Index.
Keywords: Religions